Nanodroplets Impacting on Graphene. Issue 10 (2016) - Jaques, Ygor M.; Brunetto, Gustavo; Galvão, Douglas S.
ABSTRACT: The unique and remarkable properties of graphene can be exploited as the basis to a wide range of applications. However, in spite of years of investigations there are some important graphene properties that are not still fully understood, as for example, its wettability. There are controversial reported results whether graphene is really hydrophobic or hydrophilic. In order to address this problem we have carried out classical molecular dynamics simulations of water nanodroplets shot against graphene surface. Our results show that the contact angle values between the nanodroplets and graphene surfaces depend on the initial droplet velocity value and these angles can change from 86° (hydrophobic) to 35° (hydrophilic). Our preliminary results indicate that the graphene wettability can be dependent on spreading liquid dynamics and which can explain some of the apparent inconsistencies reported in the literature.